Next generation business handbook - Chowdhury, Subir (Hoboken, NJ : John Wiley, 2004)
"The Next Generation Business Handbook gathers the knowledge and experience of promising minds from the world's top business schools, such as Harvard, Sloan at MIT, The Wharton School of the University of Pennsylvania, Kellogg at Northwestern University, Yale, London Business School, INSEAD, and IMD Switzerland, among others. Under the leadership of Subir Chowdhury, a top business thinker, these international next generation thinkers discuss every aspect of business and lay the groundwork for the key business concepts of tomorrow." "Along with addressing such special topics as career imprinting and operating in a virtual workspace, the Next Generation Business Handbook offers a complete presentation of all aspects of considerations organized around Chowdhury's own next generation business model." "The Next Generation Business Handbook is a valuable tool for managers, consultants, and researchers at all levels of business as well as students in business schools."--Jacket.
Leadership and the business environment -- Leadership and learning -- Leadership and employees -- Leadership and the workplace -- Strategies for competitive advantage -- Strategic planning and renewal -- Strategies for the networked economy -- Strategies for business expansion -- Strategies for nonprofit organizations -- Relating to the customer -- Experience with the customer -- Managing the customer -- Entrepreneurial behavior -- Entrepreneurship and finance -- Entrepreneurship and strategy -- Entrepreneurial management -- Entrepreneurship and economics -- People-management strategy -- HR management -- People and the organization -- Organizations in the networked ERA -- Network strategy.
Published simultaneously in Canada.
Includes bibliographical references (pages 1199-1262) and indexes.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Industrial management; Business; Gestion d'entreprise.; Affaires; Business; Industrial management; business (commercial function); Management Styles & Communication; Management; Business & Economics; Management